PENGARUH TERAPI BEKAM BASAH TERHADAP PERUBAHAN SKALA NYERI PADA PASIEN MIGRAIN - Mulia Mayangsari (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
The research design used was Experimental with Kunsekutive Sampling technique. The population in this study were patients who had migraine in Noreh village. The working area of Puskesmas Sreseh was 18 respondents and the result was analyzed using Shapiro Wilk and Wilcoxon test. The results of the study in migraine patients can be seen that the mean pretest scale of migraine pain scale is 4.67 whereas, for the mean posttest of migraine pain scale is 2.22. In the pretest of migraine pain scale the minimum value found is 4 whereas, the maximum value is 6. While in posttest skalanyeri migraine the minimum value found is 1 whereas, the maximum value is 3. In the Shapiro Wilk analysis showed that there were differences in the scale of migraine pain before and after wet bruise therapy. In the Wilcoxon analysis comparing migraine patients, a p-value of 0,000 indicated that there was an effect of wet-brushing therapy on changes in the pain scale. To health workers and educational institutions are expected to use wet brewing therapy as a complementary alternative and as a non-pharmacological treatment that can reduce the scale of pain.